Evaluation of a linear elastic 3D FEM to simulate rail track response under a high-speed train - Cunha, J. P. (2012)
The development of tools and methodologies that can accurately predict the behavior of high-speed lines when subjected to traffic loads has become one of the main issues of research. The work herein presented pretends to study the possibility to simulate acceleration levels at the track and soil using commercial FEM software. A 3D finite element mesh was used in order to simulate the rail track and soil in an attempt to reproduce the experimental measurements with a dynamic linear computation. The computed response at the sleeper agreed very well with the experimental measurements but the response at the soil was not as accurate. The results are discussed and explained. In the scope of the proposed objective, it is demonstrated for the case study that the use of linear elastic material models in commercial FEM software allows a reasonable prediction of track response due to the passage of a high speed train.